2021
DOI: 10.1017/gmh.2021.49
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of the symptoms of depression, anxiety, and stress during the COVID-19 pandemic in Bangladesh: a systematic review and meta-analysis

Abstract: The COVID-19 pandemic affects people's psychological well-being as well as their risk of physical complications. Under the circumstance, it is essential to synthesize the existing evidence on psychological consequences with a view to fostering policymaking. Thus, a systematic attempt was compiled to review the Bangladeshi literature related to common mental health problems (i.e. depression, anxiety, and stress) during the COVID-19 pandemic. Adhering to the PRISMA guidelines, a systematic literature search was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 47 publications
6
58
5
1
Order By: Relevance
“…The higher incidence of PTSD in married medical personnel is not entirely consistent with a meta-study ( 28 ) that reported a higher incidence of psychological stress in unmarried medical personnel than in married personnel during the COVID-19 epidemic, possibly due to cultural constraints on the incidence of PTSD that vary between countries ( 29 31 ). A study by Li et al ( 32 ) assessing Chinese medical team members during the COVID-19 epidemic supports our hypothesis.…”
Section: Discussionsupporting
confidence: 53%
“…The higher incidence of PTSD in married medical personnel is not entirely consistent with a meta-study ( 28 ) that reported a higher incidence of psychological stress in unmarried medical personnel than in married personnel during the COVID-19 epidemic, possibly due to cultural constraints on the incidence of PTSD that vary between countries ( 29 31 ). A study by Li et al ( 32 ) assessing Chinese medical team members during the COVID-19 epidemic supports our hypothesis.…”
Section: Discussionsupporting
confidence: 53%
“… 16 COVID-19 has a negative influence on psychological aspects of health reported by Akter et al 17 which further influences overall wellbeing. 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, unwanted fear, panic, and worry related to being infected with the virus, loss of beloved ones, and economic crisis occur, whereas people have been reported at a higher risk of issues such as common mental health problems (i.e., depression, anxiety, and stress) and poor physical health along with inflammatory diseases ( 5 , 11 ). Nearly half of the Bangladeshi people have been reported suffering from mental health problems (higher than the prevalence rates of mental disorders during the normal period), as estimated by a recent meta-analysis of the studies conducted during the COVID-19 pandemic ( 12 ). However, Bangladesh, like other countries, has implemented various safety precautions to mitigate the transmission, including pedestrianizing flow, confining them at home, allowing them to work from home, increasing awareness, disseminating information, closing schools, and providing other public assistance ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%